Topographic and Geodetic Survey for Samarkand's Administrative Boundaries: Survei Topografi dan Geodesi untuk Batas Administratif Samarkand - D, Obidova D.; O, Khamdamova D. (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Administrative and territorial boundary delineation is vital in the effective governance and economic planning of urban regions globally, with digital technologies increasingly integrated into these processes for accuracy and efficiency. Specific Background: In Uzbekistan, the city of Samarkand’s administrative boundaries are undergoing significant realignment as part of a broader initiative to incorporate strategic urban centers and enable digital land management across administrative zones. Knowledge Gap: Existing methods lack precise integration with digital geospatial frameworks, leaving a gap in high-resolution topographic data essential for clear administrative delineation. Aims: This study seeks to develop and apply an accurate, digitally supported methodology for determining the boundaries of Samarkand's administrative units using advanced geodetic and topographic techniques. Results: By utilizing the CREDO DAT program, this study achieved precise boundary coordinates through the automated processing of survey points, and further analysis was conducted using the Panorama program for detailed map orientation. Novelty: This research presents a unique approach by integrating CREDO DAT with geospatial tools in administrative boundary demarcation, enabling accurate and reproducible results that surpass traditional methods in efficiency and scalability. Implications: The findings support the strategic planning of Samarkand’s infrastructure and resource allocation while also laying the groundwork for applying similar methodologies in other urban regions, advancing Uzbekistan’s digital transformation efforts in land management.Highlights: Digital tools enhance accuracy in administrative boundary mapping. CREDO DAT and Panorama software streamline data processing for precise mapping. This method supports effective urban planning and resource management in Samarkand. Keywords: Administrative Zones, Border, Territory, District, City